Plasticity and the Poetics of Inside-Out Inversion in Emmett Williams and Roman Stańczak - Tomasz Sawczuk (Text Matters)
Informed by the current call for a reassessment of the concepts of radicalism and extremity in the fields of literature and visual arts, my study aims to investigate the radicalities entailed by the tactics of turning inside out the materialities of poems and artworks as exemplified, respectively, by Emmett Williams’s concrete poetry and Roman Stańczak’s sculptural works conceptualized as inverted everyday objects. Taking a cue chiefly from Catherine Malabou’s explorations of plasticity, I propose to argue that by destabilizing the interior/exterior dichotomy of the forms belonging to their respective fields, both Williams and Stańczak challenge the commonplaceness, transparency and rigidity of text, sign, and the quotidian object, thus, on the one hand, gesturing towards what the philosopher terms as “the twilight of writing” and, on the other, articulating a need for a more processual and contingent, or plastic as Malabou would have it, way of thinking about literature, art, and life. As I hope to demonstrate, by employing certain strategies to exteriorize the “insides” of the poem (the syntax, the page grid, spacing, or the shape of the grapheme), Williams foregrounds the discursive interplay of the graphic and the plastic, whereas Stańczak’s altered objects foray into inquiries on (the lack of) transcendence. The final part of my analysis seeks to envision political dimensions of both concrete poetry and Stańczak’s visual works as filtered through the lens of plasticity. The implications brought about by plastic reading, as I claim, link with new models of meaning-making and forms of resistance to ideologies of power.